Immunological Features and Potential Biomarkers of Systemic Sclerosis–Associated Interstitial Lung Disease and Idiopathic Pulmonary Fibrosis - Shuai Shao; Siyu Cao; Yusha Chen; Zhijin Zhang; Tong Zhaohui (The Clinical Respiratory Journal)
ABSTRACT Background This study aims to summarize the similarities and differences in immune cell characteristics, and potential therapeutic targets between systemic sclerosis‐associated interstitial lung disease (SSc‐ILD) and idiopathic pulmonary fibrosis (IPF). Methods This study included SSc‐ILD and SSc‐nonILD patients who were admitted to Beijing Chaoyang Hospital between April 4th, 2013, to June 30th, 2023. Publicly available datasets, including peripheral blood monocular cell (pbmc) single‐cell data, SSc, SSc‐ILD pbmc transcriptome data, and SSc‐ILD, IPF lung tissue transcriptome data were analyzed. Statistical analyses were conducted using the SPSS and R software, employing standard statistical methods and bioinformatics packages such as Seurat, DESeq2, enrichR, and CellChat. Results The results revealed that the CD4+/CD8+ T cell ratio of pbmc in SSc‐ILD patients was significantly higher than in SSc‐nonILD patients. In IPF patients, an elevated CD4+/CD8+ T cell ratio was also observed in progressive group, and Treg and mature CD4+ T cells might cause this change. JAK–STAT pathway and the cytokine–cytokine receptor interaction pathway were activated in peripheral blood T cells of IPF patients. The CD30, CD40, and FLT3 signaling pathways were found to play crucial roles in T cell interactions with other immune cells among IPF patients. SPA17 as a commonly upregulated gene among SSc, SSc‐ILD, and IPF pbmc and lung, with its expression correlating positively with disease severity and lung function progression. Conclusion CD4+/CD8+ T cell ratio might associate with ILD initiation and progression; Treg cells and mature CD4+ T cells play key roles of it. SPA17 might serve as a pan‐ILD marker and associated with lung function progression.